2005
DOI: 10.1074/jbc.m411353200
|View full text |Cite
|
Sign up to set email alerts
|

Src Phosphorylates Ezrin at Tyrosine 477 and Induces a Phosphospecific Association between Ezrin and a Kelch-Repeat Protein Family Member

Abstract: Ezrin, a linker between plasma membrane and actin cytoskeleton possesses morphogenic properties and can promote dissemination of tumor cells. Ezrin is phosphorylated on tyrosine, but a detailed picture of the signaling pathways involved in this modification is lacking. The transforming tyrosine kinase Src has various cytoskeletal substrates and is involved in regulation of cellular adhesion. We studied the role of Src in tyrosine phosphorylation of ezrin in adherent cells. We show that ezrin is phosphorylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 72 publications
4
67
0
Order By: Relevance
“…Indeed, residues 145 and 477 have been shown to be phosphorylated by Src, and inhibition of this kinase severely impairs ezrin tyrosine phosphorylation (36). On the other hand, kinase assays have shown that Tyr-353 is poorly phosphorylated by Src in vitro (36), indicating that the Src role may be indirect, allowing additional tyrosine kinases, such as those activated by epidermal growth factor (35) and hepatic growth factor (34), to phosphorylate ezrin. Because androgen treatment is known to activate Src (52), it is likely that Tyr-145 and Tyr-477 are also phosphorylated in response to androgen treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, residues 145 and 477 have been shown to be phosphorylated by Src, and inhibition of this kinase severely impairs ezrin tyrosine phosphorylation (36). On the other hand, kinase assays have shown that Tyr-353 is poorly phosphorylated by Src in vitro (36), indicating that the Src role may be indirect, allowing additional tyrosine kinases, such as those activated by epidermal growth factor (35) and hepatic growth factor (34), to phosphorylate ezrin. Because androgen treatment is known to activate Src (52), it is likely that Tyr-145 and Tyr-477 are also phosphorylated in response to androgen treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation is another mechanism whereby ezrin relays signals (26,31,34). Tyrosines 145, 353, and 477 have been identified as phosphorylation sites (35,36). Tyr-145 mediates signaling events leading to cell spreading and proliferation (26,31), whereas phosphorylation of Tyr-353 has been linked to epithelial cell survival through the activation of the PI(3) kinase/AKT pathway (31,37).…”
Section: Ezrin Overexpression Is Not Sufficient To Promote Pca Cellmentioning
confidence: 99%
“…It is indeed possible that pervanadate may activate c-Src, which could phosphorylate connexin45 directly. To this point, c-Src and Src family members have been reported to be activated by pervanadate in a diverse variety of cells (Boulven et al, 2002;Fan et al, 2003;Takahashi et al, 2004;Heiska and Carpen, 2005). On the other hand, pervanadate inhibition of phosphatases may merely permit the detection of low level, constitutive tyrosine phosphorylation caused by currently unknown tyrosine kinases.…”
Section: D) Regulation Of Connexin43 Channel Gating By the Src Tyrosimentioning
confidence: 99%
“…Ezrin is implicated in signal transduction networks both as a regulator and an effector interacting with various members of protein kinase A, Rho and phosphatidylinositol-3 kinase signaling pathways. Ezrin is the only ERM protein shown to be directly phosphorylated on tyrosine by the Src family kinases Lck and Src (Autero et al, 2003;Heiska and Carpen, 2005;Srivastava et al, 2005). The Src-induced phosphorylation on tyrosine Y477 leads to binding of a Kelch-repeat family protein KBTBD2 (Kelch-repeat and BTB/POZ domain binding 2) and Fes kinase, a member of fes/fps non-receptor protein kinase subfamily (Heiska and Carpen, 2005;Naba et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ezrin is the only ERM protein shown to be directly phosphorylated on tyrosine by the Src family kinases Lck and Src (Autero et al, 2003;Heiska and Carpen, 2005;Srivastava et al, 2005). The Src-induced phosphorylation on tyrosine Y477 leads to binding of a Kelch-repeat family protein KBTBD2 (Kelch-repeat and BTB/POZ domain binding 2) and Fes kinase, a member of fes/fps non-receptor protein kinase subfamily (Heiska and Carpen, 2005;Naba et al, 2008). Src and ezrin function cooperatively in deregulation of cell-cell contacts and scattering of carcinoma cells (Elliott et al, 2004).…”
Section: Introductionmentioning
confidence: 99%